Enhancing the sustainability of fundraising for community free food kitchens through ta’awun (mutual cooperation) - Mhd Sarif, Suhaimi; Ismail, Yusof; Abdul Wahid, Mohammad Fikri (Universal Publishers, 2024)
Purpose: This paper aims to examine the enhancement of sustainability in fundraising for community-free food kitchens through the concept of ta’awun (mutual cooperation). Design/methodology/approach: The study conducted qualitative personal interviews with three (3) activists from community-free kitchens to gather their insights and feedback on how to sustain fundraising and operations through the implementation of ta’awun. Findings: The findings revealed that ta'awun-driven partnerships, community engagement, and diversified fundraising approaches are key factors in sustaining fundraising and operations for community-free food kitchens. By forming partnerships with various stakeholders, including local businesses, organizations, and government entities, these kitchens can secure ongoing financial support and resources. Research limitations/implications: Firstly, this research highlights ta'awun's role in sustaining fundraising for community-free food kitchens. Further research can explore its mechanisms and cultural, social, and religious factors to inform effective fundraising strategies. Secondly, the research emphasizes engaging stakeholders like local businesses, organizations, and government entities. Studying their dynamics can uncover motivations and challenges, enhancing collaboration for ta'awun-driven initiatives. Practical implications: First, collaboration and partnerships with stakeholders (businesses, organizations, government) for sustained fundraising; second, community engagement through events, volunteer programs, and communication to foster ownership and a giving culture; third, diversified fundraising approaches (online campaigns, sponsorships, grants, crowdfunding) for financial stability, and fourth, continuous evaluation and adaptation of fundraising strategies based on feedback and changing circumstances. Originality/value: This research explores ta'awun’s role in sustaining fundraising for community-free food kitchens. It highlights the importance of community engagement and diversified fundraising approaches, providing practical insights. Additionally, it recognizes the societal impact of these kitchens in addressing food insecurity and promoting social equity.